Applications of Mittag-Leffer Type Poisson Distribution to a Subclass of Analytic Functions Involving Conic-Type Regions. (27th July 2021) - Khan, Muhammad Ghaffar; Ahmad, Bakhtiar; Khan, Nazar; Mashwani, Wali Khan; Arjika, Sama; Khan, Bilal; Chinram, Ronnason
Abstract : In this article, we introduce a new subclass of analytic functions utilizing the idea of Mittag-Leffler type Poisson distribution associated with the Janowski functions. Further, we discuss some important geometric properties like necessary and sufficient condition, convex combination, growth and distortion bounds, Fekete-Szegö inequality, and partial sums for this newly defined class.